Semileptonic Decays of B(Bs) to Light Tensor Mesons - Reza Khosravi; S. Sadeghi (Advances in High Energy Physics)
The semileptonic Bs(B)→K2⁎(a2,f2)lν, l=τ,μ, transitions are investigated in the frame work of the three-point QCD sum rules. Considering the quark condensate contributions, the relevant form factors of these transitions are estimated. The branching ratios of these channel modes are also calculated at different values of the continuum thresholds of the tensor mesons and compared with the obtained data for other approaches.